Salsolinol—neurotoxic or Neuroprotective? - Kurnik-Łucka, Magdalena (Neurotox Res, 2019)
Salsolinol (6,7-dihydroxy-1-methyl-1,2,3,4-tetrahydroisoquinoline), widely available in many edibles, is considered to alter the function of dopaminergic neurons in the central nervous system and thus, multiple hypotheses on its either physiological and/or pathophysiological role have emerged. The aim of our work was to revisit its potentially neurotoxic and/or neuroprotective role through a series of both in vitro and in vivo experiments. Salsolinol in the concentration range 10–250 μM did not show any significant release of lactate dehydrogenase from necrotic SH-SY5Y cells and was able in the concentration of 50 and 100 μM to rescue SH-SY5Y cells from death induced by H(2)O(2). Its neuroprotective effect against neurotoxin 6-hydroxydopamine was also determined. Salsolinol was found to decrease significantly the reactive oxygen species level in SH-SY5Y cells treated by 500 μM H(2)O(2) and the caspase activity induced by 300 μM of H(2)O(2) or 100 μM of 6-hydroxydopamine. Serum levels of TNFα and CRP of salsolinol-treated rats were not significantly different from control animals. Both TNFα and CRP served as indirect markers of neurotoxicity and/or neuroprotection. Although the neurotoxic properties of salsolinol have numerously been emphasized, its neuroprotective properties should not be neglected and need greater consideration.